Hypertension Knowledge, Attitude, and Practice in Adult Hypertensive Patients at a Tertiary Care Hospital in Sri Lanka - Udaya Ralapanawa; Kameera Bopeththa; Noorika Wickramasurendra; Sampath Tennakoon (International Journal of Hypertension)
Objective. Hypertension (HTN) remains a major risk factor for cardiovascular diseases globally. Despite considerable improvement in increasing awareness, treatment, and control of HTN, undiagnosed and uncontrolled HTN remains a major public health challenge. Our focus was on studying the knowledge, attitude, and practice regarding HTN in adult hypertensive patients at a tertiary care hospital in Sri Lanka. Methodology. A descriptive study on knowledge, attitude, and practice of hypertensive patients on antihypertensive medications attending the hypertensive clinic was carried out from January 2016 to June 2016 at THP. Results. The study was on a total of 371 hypertensive patients comprising 253 (68.2%) females and 118 (31.8%) males. Among the total participants, 12 (3.2%), all females, had never been to school. About half of them (47.7%) had not even reached GCE (ordinary level). More than two-thirds (77%) of the study population were aware of the complications of HTN as they were informed by a health care team member. About 74% of them were taking all their prescribed medications. Almost all (95%) patients had checked their blood pressure (BP) during the previous 12 months, and almost the same percentage had visited their doctor for BP checkups every 1–3 months. Conclusion. Our patients were well aware of the importance of regular follow-ups and also knowledgeable about the complications related to HTN. Almost 75% of the patients had optimum drug compliance. It was revealed that forgetfulness was the frequent cause for poor drug compliance.